Cultural Management and Organizational Creativity in Educational Institutions (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2021)
The article presents a study aimed at understanding cultural management and organizational creativity through the experience of educational managers and school cultural promoters, with the goal of developing the necessary theoretical framework to guide the application of these processes in the schools under study. The findings reveal that these aspects are interdependently linked within educational managerial praxis. The research was framed within a qualitative paradigm, combining ethnographic and phenomenological methods, along with their techniques and instruments for data collection and categorization. The study concludes by highlighting weaknesses among school administrators, evidenced by the lack of authentic cultural management and limited use of creativity within educational institutions. As a contribution, it provides a theoretical construct to support educational managerial practice with cultural and creative competencies.